The Ultrasound-Based Diagnosis of Sudden Scrotal Enlargement in an Infant: A Case Report - Rutka, Bartosz; Rutka, Martyna; Niedziela, Adam; Domoń, Dominik (Quality in Sport, 2025)
Scrotal enlargement in infants has a variety of causes, ranging from benign conditions like hydrocele to more serious issues such as scrotal hernias or testicular tumors. We present the case of a 3-month-old infant with progressive right-sided scrotal swelling, diagnosed with a scrotal hernia through an urgent ultrasound examination. The ultrasound revealed intestinal loops within the scrotum, confirming the diagnosis and ruling out complications such as incarceration. This case underscores the pivotal role of ultrasonography as a first-line, non-invasive diagnostic tool for scrotal conditions in infants, facilitating timely surgical intervention and preventing long-term complications.